1986
DOI: 10.1287/mnsc.32.1.56
|View full text |Cite
|
Sign up to set email alerts
|

“Lottery Equivalents”: Reduction of the Certainty Effect Problem in Utility Assessment

Abstract: This note describes a simple procedure for assessing utility functions which avoids many difficulties of the standard techniques. The conventional methods suffer from at least three drawbacks; they (1) generate utility functions that depend on the probability levels used; (2) chain responses from one question to the next, so that any bias is propagated and even magnified; and (3) change ranges and reference points constantly, introducing range effects and other distortions. Noting the evidence linking the depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(80 citation statements)
references
References 7 publications
2
75
0
3
Order By: Relevance
“…To that end, we conducted a survey amongst the general population (N=300) asking VEI questions using the operationalization of Murray et al's proposal suggested by Nord [3]. Respondents were also interviewed using the conventional PTO method and a variant of the SG proposed by McCord and de Neufville [10] that they called the "lottery equivalent" (LE) method.…”
Section: Elicitation Techniquesmentioning
confidence: 99%
“…To that end, we conducted a survey amongst the general population (N=300) asking VEI questions using the operationalization of Murray et al's proposal suggested by Nord [3]. Respondents were also interviewed using the conventional PTO method and a variant of the SG proposed by McCord and de Neufville [10] that they called the "lottery equivalent" (LE) method.…”
Section: Elicitation Techniquesmentioning
confidence: 99%
“…Both probability weighting and loss aversion are modeled by prospect theory, currently the most influential descriptive model of decision under risk. A difficulty in measuring utility under prospect theory is that the methods that are commonly used to measure utility, such as the probability, certainty equivalence, and lottery equivalence methods (Farquhar 1984, McCord andde Neufville 1986) are no longer valid because they do not take account of probability weighting and loss aversion. Wakker and Deneffe's (1996) trade-off method is robust to probability weighting when all outcomes are of the same sign, but is not able to handle loss aversion.…”
Section: Introductionmentioning
confidence: 99%
“…It thus remains possible that loss aversion is one (though probably not the sole) cause of the observed internal inconsistency. If we accept that this explanation is plausible, further tests of internal consistency ought to be undertaken (1) after mitigating loss aversion with a more sophisticated internalisation of this psychological process in the standard gamble valuation procedure (Bleichrodt, Pinto, & Wakker, 2001;Oliver, 2003), and/or (2) on alternatives to the standard gamble that intuitively induce less loss aversion (McCord & de Neufville, 1986). These tasks are beyond the scope of this article, but both offer scope for interesting and potentially important research.…”
Section: Resultsmentioning
confidence: 99%